An application of organizational excellence assessment: Evidence from cement industry - Hadi Pazoki Toroudi; Sarineh Naderi Alamdardehi; Nasim Mahjoub; Alireza Sheydaei Ardestani (Management Science Letters)
The objective of this paper is to evaluate the performance of Kiasar cement factory based on EFQM model. The study performs a survey among 26 managers and expertise and the required information is gathered in terms of five perspectives based on 23 questions arranged in Likert spectrum. Cronbakh’s α coefficient for enabling and results criteria are 0.924 and 0.950, respectively, which confirms the reliability of the questionnaire. In evaluating the data, it is revealed that employees’ scale, maintained the most difference (70.61%) and processes scale, retained the least difference (52.42%) from the ideal circumstances. Next, employees’ performance has maintained the most difference (90.79%) and customer performance, and the customer results’ scale have kept the least difference (58.27%) from the ideal situation. Kiasar cement factory has acquired 198.06 points out of 500 points of empowering scale and 164.08 points out of 500 total points of result scales. Also empowerment scales in Kiasar cement factory have acquired 39.61% of optimal score and differs from ideal circumstances around 60.39%. The results scales has acquired 32.82% of optimal score and approximately is different from ideal situation around 67.18%. The research results show that Kiasar cement factory has acquired 361.9 points out of 500 scores of EFQM.